2012
DOI: 10.1001/jama.2012.36914
|View full text |Cite
|
Sign up to set email alerts
|

Association Between a Medical School Admission Process Using the Multiple Mini-interview and National Licensing Examination Scores

Abstract: ODERN CONCEPTIONS OF medical practice demand more of practitioners than a strong knowledge base. 1 By emphasizing compassionate care, professionalism, and interpersonal skill, the Accreditation Council for Graduate Medical Education core competencies indicate that physicians are expected to possess strong personal qualities distinct from academic achievement. 2 There is evidence of a link between these aspects of practice and quality of care. [3][4][5][6][7] At the level of medical school admissions, incoming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
101
2
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 29 publications
7
101
2
3
Order By: Relevance
“…In medical schools, it is predictive of performance-students accepted via an MMI process to medical school scored higher on a national licensing examination when compared to students who were not accepted via the same MMI process, but were ultimately accepted at other medical schools. 11 Additionally, MMI scores predict experiential performance, with higher MMI scores correlating with higher clinical clerkship performance ratings for medical students. 16 Because the MMI format is used to a limited extent in pharmacy education and training, 5,9,13 additional studies are needed to validate the individual MMI stations and overall approach and to characterize predictive relationships with key outcome variables.…”
Section: Discussionmentioning
confidence: 99%
“…In medical schools, it is predictive of performance-students accepted via an MMI process to medical school scored higher on a national licensing examination when compared to students who were not accepted via the same MMI process, but were ultimately accepted at other medical schools. 11 Additionally, MMI scores predict experiential performance, with higher MMI scores correlating with higher clinical clerkship performance ratings for medical students. 16 Because the MMI format is used to a limited extent in pharmacy education and training, 5,9,13 additional studies are needed to validate the individual MMI stations and overall approach and to characterize predictive relationships with key outcome variables.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews summarizing the current state of findings on the predictive validity of medical school selection measures conclude that there is no evidence regarding the predictive validity of traditional noncognitive measures [4,11,14]. As for novel noncognitive measures, studies of MMI have indicated good predictive validity with respect to performance criteria from the early stages of medical school through licensing examinations [12,[15][16][17][18]. As expected, predictive validity visa-vis assessments that focus on clinical aspects of medicine is higher.…”
Section: Introductionmentioning
confidence: 98%
“…McMaster University reported that those students who were admitted using the MMI scored higher on the Canadian national licensing examination when compared to students admitted at other schools not using the MMI [9]. Additional studies have shown that varied approaches utilizing the MMI are reliable as a predictor of in-program performance [10], are acceptable to applicants, and may be predictive of successful performance in medical school and on pre-residency licensure examinations [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this curricular structure, VTCSOM selected the MMI to be one of the primary components of the admissions process based on the research suggesting predictive aspects of non-cognitive qualities for learning [10][11][12]. A more holistic admission process was chosen in an effort to matriculate students with a unique set of characteristics and skills, above and beyond traditional academic qualifications.…”
Section: Introductionmentioning
confidence: 99%